The Water Diffusion of Brain Following Hypoglycemia in Rats – A Study with Diffusion Weighted Imaging and Neuropathologic Analysis. (15th June 2019) - Tong, Fang; Zou, Yijuan; Liang, Yue; Lei, Hao; Lopsong, Tenzin; Liu, Yuluo; Le Grange, Jehane Michael; He, Guanglong; Zhou, Yiwu
Abstract: We established hypoglycemic rat models and divided them into three groups (the sham group, the acute hypoglycemia group and the recovery group). The brain water diffusion was examined using DWI. Thereafter, neuropathologic examinations were performed in order to evaluate the distribution of brain damage. The expression of AQP4 and Caspase3 was also examined using Western blot. We aimed to determine the specific brain regions which were vulnerable to hypoglycemia in relation to the water diffusion and neuropathology. The DWI scanning showed abnormal water diffusion in the cortex, hippocampus and hypothalamus during each stage of hypoglycemia. In the acute hypoglycemia group, the apparent diffusion coefficient (ADC) of the dentate gyrus (DG) and the hypothalamus was increased, while the ADC of the somatosensory cortex (SSc), subcortex and striatum (Str) was decreased. After glucose reperfusion and a 7-day recovery period, most of the hypoglycemia-induced changes in ADC returned to normal, except in the hypothalamus, posterior SSc and DG, which demonstrated increased ADC levels. The lowest AQP4 expression was observed in the cortex of the acute hypoglycemia group. Furthermore, there was increased Caspase3 expression in the hippocampus of the recovery group. The expression of Caspase3 in the hypothalamus was most prominent in the acute hypoglycemia group. Our work revealed that hypoglycemia significantly influenced the water diffusion of the brain. The decrease of AQP4 was associated with the formation of cytotoxic edema in acute hypoglycemia. Hypoglycemia primarily tends to damage the cerebral cortex, hippocampus and hypothalamus and may result in permanent injury to the brain. Highlights: Severe hypoglycemia can significantly influence the water diffusion of the brain. The downregulation of AQP4 is associated with the formation of cytotoxic edema in acute hypoglycemia. The cerebral cortex, hippocampus and hypothalamus are specific regions vulnerable to severe hypoglycemia.